The Role of Ownership Structure in Companies Listed on the Indonesia Stock Exchange: A Literature Review - Nugroho, Ady Setyo (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Companies that have issued their shares on the Indonesian stock exchange are companies whose shares can be traded. This creates an ownership structure within the company. The ownership structure certainly determines the company's goals and going concerns. This research method is a literature review with a qualitative approach. The results obtained include that the ownership structure has several important roles including: 1) supervision; 2) internal control; 3) tax avoidance; and 4) firm performance.